Beta-blockers and Traumatic Brain Injury: A Systematic Review, Meta-analysis, and Eastern Association for the Surgery of Trauma Guideline. Issue 6 (December 2017) - Alali, Aziz S.; Mukherjee, Kaushik; McCredie, Victoria A.; Golan, Eyal; Shah, Prakesh S.; Bardes, James M.; Hamblin, Susan E.; Haut, Elliott R.; Jackson, James C.; Khwaja, Kosar; Patel, Nimitt J.; Raj, Satish R.; et al.
Abstract : Objective: To determine if beta-(β)-blockers improve outcomes after acute traumatic brain injury (TBI). Background: There have been no new inpatient pharmacologic therapies to improve TBI outcomes in a half-century. Treatment of TBI patients with β-blockers offers a potentially beneficial approach. Methods: Using MEDLINE, EMBASE, and CENTRAL databases, eligible articles for our systematic review and meta-analysis (PROSPERO CRD42016048547) included adult (age ≥ 16 years) blunt trauma patients admitted with TBI. The exposure of interest was β - blocker administration initiated during the hospitalization. Outcomes were mortality, functional measures, quality of life, cardiopulmonary morbidity (e.g., hypotension, bradycardia, bronchospasm, and/or congestive heart failure). Data were analyzed using a random-effects model, and represented by pooled odds ratio (OR) with 95% confidence intervals (CI) and statistical heterogeneity (I 2 ). Results: Data were extracted from 9 included studies encompassing 2005 unique TBI patients with β - blocker treatment and 6240 unique controls. Exposure to β - blockers after TBI was associated with a reduction of in-hospital mortality (pooled OR 0.39, 95% CI: 0.27–0.56; I 2 = 65%, P < 0.00001). None of the included studies examined functional outcome or quality of life measures, and cardiopulmonary adverse events were rarely reported. No clear evidence of reporting bias was identified. Conclusions: In adults with acute TBI, observational studies reveal a significant mortality advantage with β-blockers; however, quality of evidence is very low. We conditionally recommend the use of in-hospital β-blockers. However, we recommend further high-quality trials to answer questions about the mechanisms of action, effectiveness on subgroups, dose-response, length of therapy, functional outcome, and quality of life after β-blocker use for TBI. Abstract : Supplemental Digital Content is available in the text